A study to evaluate scope of preventive strategies in modifiable risk factors of hypertension - Mathur, Medha; Mathur, Navgeet (International Journal Of Community Medicine And Public Health, 2018)
Background: Hypertension is a vascular disorder associated with high morbidity and mortality. Risk factor prevention plays key role in control of the non-communicable diseases. Current study was conducted to assess prevalence of risk factors related to hypertensive patients. Methods: This cross-sectional study was conducted for the period of six months (January to June 2018). Total 672 hypertensive patients were included in this study and subjected to evaluation of modifiable risk factors like obesity, lack of exercise, smoking, dyslipidemia and pre-existing diabetes mellitus along with non-modifiable risk factors like positive family history and age. Results: On risk factor evaluation of 672 hypertensive patients it was found that 601(89.4%) patients had lack of exercise, 210 (31.2%) patients had dyslipidemia, 190 (28.2%) patients were smokers, 164 (24.4%) patients had diabetes mellitus before emergence of hypertension, 132 (19.6%) patients were obese and 498 (74.1%) patient had age more than 60 years, 94 (13.9%) patients had family history of hypertension. Conclusions: High prevalence of risk factors for this non-communicable disease in Indian community is alarming. Dealing with modifiable risk factors by health education, promotion of exercise, favourable life style, dietary modifications, cessation of smoking, screening programmes for early detection of deranged blood pressure, blood sugar, lipid profile can be effective preventive strategies.